2003
DOI: 10.1007/bf02940101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the botanical composition and weather conditions on mycotoxins in winter forage from grassland

Abstract: The paper focuses on possible effects of the botanical composition and weather conditions on the extend of zearalenone and ochratoxin A concentrations in various grass swards in winter pasture systems. Zearalenone is only detectable in pure stands ofLolium perenne or inLolio-Cynosuretum plant communities, respectively. The occurrence of ochratoxin A is more frequent and less specific concerning the botanical composition. This mycotoxin was found in both,Lolium perenne andFestuca arundinacea in varying years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Comparing the contents of ergosterol and zearalenone in forage it is obvious that the high ergosterol content not always relates to the high content of zearalenone. This fact is corroborated also by Laser et al (2003), who claim that the high content of ergosterol need not necessarily indicate a high content of mycotoxins. However, namely the Arrhenatherum elatius forage in the second year of monitoring exhibited in December not only higher ergosterol content but also clearly related higher zearalenone content.…”
Section: Discussionsupporting
confidence: 53%
“…Comparing the contents of ergosterol and zearalenone in forage it is obvious that the high ergosterol content not always relates to the high content of zearalenone. This fact is corroborated also by Laser et al (2003), who claim that the high content of ergosterol need not necessarily indicate a high content of mycotoxins. However, namely the Arrhenatherum elatius forage in the second year of monitoring exhibited in December not only higher ergosterol content but also clearly related higher zearalenone content.…”
Section: Discussionsupporting
confidence: 53%
“…However, in the sward pre‐utilized in August, there was a higher proportion of perennial ryegrass as described in the experiment by Golinska and Golinski (2005), which was more infected by Fusarium fungi than other grass species. Laser et al. (2003) also suggested that ZEA was only detectable in pure stands of L. perenne or in Lolio‐Cynosuretum plant communities.…”
Section: Resultsmentioning
confidence: 98%
“…The hypothesis of the equality of harvest dates was rejected because differences in the concentration of ERG and ZEA were statistically significant. However, according to Laser et al. (2003) high amounts of ergosterol do not necessarily have to be an indication of high ZEA and OA concentrations in herbage, which is worth emphasizing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wilting reduced the content of fungi but led to a higher content of mycotoxins. According to Laser et al (2003), the high content of ergosterol need not necessarily indicate a high content of mycotoxins. In the comparison of the content of deoxynivalenol and zearalenone, the silage contained especially deoxynivalenol.…”
Section: Discussionmentioning
confidence: 99%